2015
DOI: 10.1287/opre.2015.1361
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Optimization Over Randomization in Designing Experiments Involving Small Samples

Abstract: Random assignment, typically seen as the standard in controlled trials, aims to make experimental groups statistically equivalent before treatment. However, with a small sample, which is a practical reality in many disciplines, randomized groups are often too dissimilar to be useful. We propose an approach based on discrete linear optimization to create groups whose discrepancy in their means and variances is several orders of magnitude smaller than with randomization. We provide theoretical and computational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 18 publications
(16 reference statements)
3
60
0
Order By: Relevance
“…Fixing ρ >0 and endowing F=span{1,x1,,xd,x12/ρ,,xd2/ρ,x1x2/false(2italicρfalse),,xd1xd/false(2italicρfalse)} with the ∞‐norm and normalizing the data will recover the method of Bertsimas et al . (), which optimizes the balance in covariate means and centred second moments by using mixed integer programming.…”
Section: The Effect Of Structural Information and Lack Thereofmentioning
confidence: 99%
See 2 more Smart Citations
“…Fixing ρ >0 and endowing F=span{1,x1,,xd,x12/ρ,,xd2/ρ,x1x2/false(2italicρfalse),,xd1xd/false(2italicρfalse)} with the ∞‐norm and normalizing the data will recover the method of Bertsimas et al . (), which optimizes the balance in covariate means and centred second moments by using mixed integer programming.…”
Section: The Effect Of Structural Information and Lack Thereofmentioning
confidence: 99%
“…This both generalizes and formalizes an observation that was made by Bertsimas et al . (). We develop algorithms for computing optimal designs by using mixed integer programming and semidefinite programming and provide hypothesis tests for these designs.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Utilizing baseline information to an even greater degree than in the stratification case, some researchers have recently suggested relying on optimization instead of randomization for assigning treatment status to subjects. Bertsimas, Johnson, and Kallus () propose a method based on discrete linear optimization, such that assignment is chosen to minimize the discrepancy between treatment groups in terms of means and variances of covariates. Kasy () considers the experiment as a statistical decision problem where the goal is to find the unique treatment assignment that minimizes a Bayesian or minimax risk function (based on the mean squared error of a point estimator).…”
Section: Dozen Thingsmentioning
confidence: 99%
“…They suggested developing plans that are robust to time effects in order to obtain null covariance between variables and time. Bertsimas et al (2015) also showed the benefits of the systematic approach in experiments with "guinea pigs", by applying mathematical optimization techniques. Ganju & Lucas (2004) studied the systematic sequencing of the experiments' order, and they indicated the inadequacy of the randomization as a practice to be followed in any situation.…”
Section: Two-level Factorial Experimental Designs In the Presence Of mentioning
confidence: 99%